Highly Selective Deethylation of Rhodamine B on TiO2 Prepared in Supercritical Fluids. (1st August 2011) - Fan, Yuzun; Chen, Guoping; Li, Dongmei; Luo, Yanhong; Lock, Nina; Jensen, Anca Paduraru; Mamakhel, Aref; Mi, Jianli; Iversen, Steen B.; Meng, Qingbo; Iversen, Bo B.
Abstract : Pure phase anatase TiO2 nanoparticles with sizes of 5–8 nm and varying crystallinity were synthesized in supercritical isopropanol/water using a continuous flow reactor. Their photodegradation of rhodamine B (RhB) was evaluated under visible light irradiation. The as-prepared TiO2 nanoparticles show much higher photodegradation efficiencies than commercial Degussa P25 TiO2 . Moreover, the photodegradation of RhB on the as-prepared TiO2 follows a different process from that on P25 TiO2, quicker N-deethylation and slower cleavage of conjugated chromophore structure. Based on PXRD, TEM, and BET measurements, these two photodegradation properties have been explained by the physicochemical properties of TiO2 .